Evaluation of the Reference Guide III Questionnaire of NOM-035-STPS-2018: Limitations, Implications, and Challenges of its Validity - Martínez-Mejía, Emmanuel (Consorcio de Universidades Mexicanas A.C., 2023)
The aim of this research is to evaluate the content, construct, and criterion validity, as well as the reliability of the GRIII questionnaire of NOM-035-STPS-2018 among tertiary economic activity workers in Mexico City. The method was proposed in three phases: 1) Content validity: specification tables based on the same NOM-035 and its GRIII. 2) Construct validity: confirmatory factor analysis of the domains, with a sample of 1,179 workers. 3) Criterion validity: multiple linear regression models of the domains on a measure of anxiety, with a sample of 432 workers. The results indicate validity limitations of the GRIII questionnaire, which implies questioning its effectiveness. The challenge is posed to the corresponding authorities to reinforce the questionnaire or redesign a new one when the standard is revised.